Decreasing Incidence of Symptomatic Epstein‐Barr Virus Disease and Posttransplant Lymphoproliferative Disorder in Pediatric Liver Transplant Recipients: Report of the Studies of Pediatric Liver Transplantation Experience. Issue 7 (25th June 2013) - Narkewicz, Michael R.; Green, Michael; Dunn, Stephen; Millis, Michael; McDiarmid, Susan; Mazariegos, George; Anand, Ravinder; Yin, Wanrong; ,
<x xml:space="preserve">Abstract</x> Posttransplant lymphoproliferative disorder (PTLD) causes significant morbidity and mortality in pediatric recipients of liver transplantation (LT). Objective: Describe the incidence of PTLD and symptomatic Epstein‐Barr virus (SEBV) disease in a large multicenter cohort of children who underwent LT with a focus on the risk factors and changes in incidence over time. SEBV and PTLD were prospectively determined in 2283 subjects who had undergone LT for the first time with at least 1 year of follow‐up in the Studies of Pediatric Liver Transplantation database. SEBV was defined with specific criteria, and PTLD required tissue confirmation. The incidence of SEBV and PTLD was determined with a Kaplan‐Meier analysis. Univariate and multivariate modeling of risk factors was performed with standard methods. SEBV occurred in 199 patients; 174 (87.4%) were EBV–negative at LT. Seventy‐five patients developed PTLD, and 64 (85.3%) of these patients were EBV‐negative at LT. Among the 2048 patients with at least 2 years of follow‐up, 8.3% developed SEBV by the second year after LT, and 2.8% developed PTLD. There were lower rates of SEBV (5.9% versus 11.3%, P < 0.001) and PTLD (1.7% versus 4.2%, P = 0.001) in 2002‐2007 versus 1995‐2001. In 2002‐2007, tacrolimus and cyclosporine trough blood levels in the first year after LT were significantly lower, and fewer children were receiving steroids. Biliary atresia, and recipient EBV status were correlated. In a multivariate analysis, era of LT, recipient EBV status, and frequent rejection episodes were associated with SEBV and PTLD. The incidence of SEBV and PTLD is decreasing in pediatric LT recipients concomitantly with a reduction in immunosuppression. Younger recipients and those with multiple rejections remain at higher risk for SEBV and PTLD. Liver Transpl 19:730–740, 2013.. © 2013 AASLD.